Comparison of Nutrient Content in Fruit of Commercial Cultivars of Eggplant (Solanum melongena L.) - Ayaz Faik Ahmet; Colak Nesrin; Topuz Mujgan; Tarkowski Petr; Jaworek Pavel; Seiler Gerald; Inceer Huseyin (Polish Journal of Food and Nutrition Sciences)
Eggplant (Solanum melongena L.) is one of the most popular common major vegetable crops worldwide. This study evaluated the nutritional content of seven commercial eggplant fruits in terms of fatty acid, mineral, sugar, organic acid, amino acid and polyamine contents. The most abundant fatty acid was linoleic acid (range, 39.14-53.81%, ave. 45%), and the most abundant mineral was K (range, 1556.2-3171.6 mg/kg fw, ave. 2331.9). The major organic acid was malic acid (range, 129.87-387.01 mg/g fw, ave. 157.49), and the major sugar was fructose (range, 1242.81- 1379.77 mg/100 g fw, ave. 1350.88). The major polyamine was putrescine (11.54 and 25.70 nmol/g fw, ave. 17.86), and the major amino acid was glutamine (148.4 and 298.75 mg/100 g fw, ave. 219.74). Overall, taking into account the export potential of eggplants, these results may contribute to further studies aiming to improve other nutrient-rich varieties of eggplant in breeding programs.